The metaphysics of theism : Aquinas's natural theology in Summa contra gentiles I - Kretzmann, Norman (Clarendon Press, 1997)
Norman Kretzmann expounds and criticises Aquinas' theology of creation, which is natural (or philosophical) in that Aquinas developed it without depending on the data of Scripture.